Assessing a potential role of host Pannexin 1 during Chlamydia trachomatis infection. - Mary J McKuen; Gerhard Dahl; Kenneth A Fields (PLoS ONE, 2013)
Pannexin 1 (Panx1) is a plasma membrane channel glycoprotein that plays a role in innate immune response through association with the inflammasome complex. Probenecid, a classic pharmacological agent for gout, has also been used historically in combination therapy with antibiotics to prevent cellular drug efflux and has been reported to inhibit Panx1. As the inflammasome has been implicated in the progression of Chlamydia infections, and with chlamydial infections at record levels in the US, we therefore investigated whether probenecid would have a direct effect on Chlamydia trachomatis development through inhibition of Panx1. We found chlamydial development to be inhibited in a dose-dependent, yet reversible manner in the presence of probenecid. Drug treatment induced an aberrant chlamydial morphology consistent with persistent bodies. Although Panx1 was shown to localize to the chlamydial inclusion, no difference was seen in chlamydial development during infection of cells derived from wild-type and Panx1 knockout mice. Therefore, probenecid may inhibit C. trachomatis growth by an as yet unresolved mechanism.